RESEARCH OF THE SAFETY OF THE FAT COMPONENT OF CAPSULATED FORMS OF SPECIALIZED PRODUCTS - E. Y. Wolf; I. V. Simakova; A. A. Wolf (Современная наука и инновации, 2022)
Polyunsaturated fatty acids (PUFA) are widely used in high performance sports and fitness. It is worth noting their ability to reduce muscle damage and the inflammatory response after strength loads, improve the function of external respiration and normalize the athlete's body composition. Nevertheless, the direct use of PUFAs in food and beverages is limited by their low solubility in water and high sensitivity to oxidation, and therefore various antioxidants are introduced into their composition, a striking representative of which is astaxanthin, which, according to various scientific data, demonstrates effective use as a nutritional support, providing the body with the necessary elements for its construction and renewal, supplying the necessary amount of energy and substances involved in the regulation of physiological processes, as well as weakening vascular remodeling, suppressing the proliferation of vascular smooth muscle cells, improving the function of mitochondria. However, there are practically no works devoted to the study of various safety forms of PUFAs during storage. Nevertheless, they can be a potential source of danger to the body, due to the fact that during the oxidation process, oxidation products are formed, such as glycidol ethers, epoxides, secondary oxidation products, insoluble in petroleum ether, which have teratogenic, mutagenic and carcinogenic effects. In this regard, the aim of our study is to compare the biological effectiveness and safety of encapsulated forms of PUFAs with and without an antioxidant. The work uses generally accepted methods that normalize the safety and quality offats, regulated by the All-Russian Research Institute of Fats. The following indicators were investigated: determination of the concentration of epoxides; determining the acid number by reaction with concentrated phosphoric acid; peroxide number by reaction with sodium thiosulfate; determination of the total content of oxidation products insoluble in petroleum ether. As a result of the study of the fat component of the test samples, the acid number is 5.8 mg KOH / g, which is twice the maximum allowable value. These are not stable components, they react with each other or with other oxidation products and their content varies. The amount of epoxides in the studied capsules is 48.4 mmol / kg, which is approximately twice the permissible level, which cannot but cause concern for scientists around the world. The number of epoxides is not standardized in any of the regulatory and technical documents, but scientific studies have proven that these products are toxic. The safety indicators of the fat component regulated by the technical regulations of the Customs Union do not fully reflect the safety requirements for the fat component of biologically active additives, since there are no standards for the most important safety indicators of fats - the content of secondary oxidation products.